Prospective randomized controlled study of patient compliance in using a compression stocking: Importance of recommendations of the practitioner as a factor for better compliance. (February 2018) - Uhl, Jean-François; Benigni, Jean-Patrick; Chahim, Maxime; Fréderic, Delinotte
Background: Patient compliance is the cornerstone of compression therapy success. However, there has been up to now no tool to assess it other than self-reporting by the patient, which is not reliable. Material and methods: Forty active females classified C2S were enrolled to wear compression stockings (CS) providing a pressure of 15–20 mmHg at the ankle. A thermal probe was inserted in the stocking (Thermotrack®), recording the skin temperature every 20 min for four weeks. The patients were randomized in two groups of 20: – Group 1: Receiving minimal recommendations by their physician at the office. – Group 2: Receiving in-depth recommendations by the physician reinforced with SMS message which were repeated once a week for four weeks. The basic CEAP classification and the quality of life (QoL) were recorded before and after four weeks. Results: The two groups are similar for age, symptoms and type of CS. The analysis of the thermal curves showed a significant increase (+33%) in the average wearing time daily in the group 2: 8 h vs. 5.6 h (group1) p  < 0.01. The average number of days worn per week is also increased: 3.4 (group 1) vs. 4.8 (group 2), thus improving patient compliance from 48.5% to 70% as a direct result of the physician recommendations ( p  < 0.001). Conclusion: This is the first study assessing the real compliance in CVD patients of using compression. It shows that better and repeated recommendations by the practitioner result in an increase in time the compression is used by 33%. The study also suggests that the number of days the compression stocking is worn is a good criterion of patient compliance.